Intention to appoint legitimate tax agents among sole proprietorships in Negeri Sembilan, Malaysia - Marimuthu, Munusamy; Ibrahim, Che Mohd Zaradi (2018)
In this study, Ajzen’s (1991) Theory of Planned Behavior (TPB) is used as a theoretical framework to answer the theoretical gap and practical gap according to the Inland Revenue Board (IRBM) Media statement dated 26 November 2015 that remind all Malaysian taxpayers to only seek legitimate (approved) tax agent services to manage their tax matters. The objectives of this study are to examine the factors that determine the intention of sole proprietor taxpayers to appoint or to use legitimate tax agents and to determine also whether attitude, subjective norm, self-efficacy and tax enforcement will influence their intention to appoint legitimate tax agents. The data set of the study was obtained from the survey method using questionnaires applied to 313 sole p proprietor taxpayers who visited the IRBM Seremban Branch Office during Taxpayers’ Service Month (or Hasil4U) programme held on 1 March until 30 June 2016. Samples were chosen by using the random sampling technique. The result of the reliability test shows that the research instrument is in an acceptable position. The study found all the determinants of intention studied were having a mean score of 3.44 which show that there is a high intention for sole proprietor taxpayers to use legitimate tax agents. Multiple regression analysis was carried out on the data collected to see the relationship between the independent and dependent variables. The result of multiple regression shows that the independent variables tested can explain 91.6% variances towards the intention to use legitimate tax agents. Consistent with the hypotheses developed, the results reveal that attitude, subjective norm and tax enforcement has significant positively related to the intention of the respondents. Nevertheless, self- efficacy has the significant negative statistical effect to the intention of the respondents.